THE IMPLEMENTATION OF PROLOG INTERPRETER: LEXICAL AND SYNTAX ANALYSES - Tsimbal, Alexander (International Journal of Computing, 2014)
The article considers the development of Prolog programming language interpreter with lexical and syntax analyzer, table control and interpreter blocks. There is proposed the schemes of syntax analyzes and the elements of translator’s program code. The software is developed in Visual C++ 2005 (Beta) environment.